2012
DOI: 10.1289/ehp.1205006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Geostatistical Interpolation and Remote Sensing Techniques for Estimating Long-Term Exposure to Ambient PM2.5Concentrations across the Continental United States

Abstract: Background: A better understanding of the adverse health effects of chronic exposure to fine particulate matter (PM2.5) requires accurate estimates of PM2.5 variation at fine spatial scales. Remote sensing has emerged as an important means of estimating PM2.5 exposures, but relatively few studies have compared remote-sensing estimates to those derived from monitor-based data.Objective: We evaluated and compared the predictive capabilities of remote sensing and geostatistical interpolation.Methods: We developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 26 publications
6
55
0
Order By: Relevance
“…Additionally, we also found that CV IS errors of PM 2.5 Optimal tended to be lower at the testing sites, which were surrounded by more training sites ( Figure 5). Similar findings have been reported in previous studies, which introduced spatial or spatiotemporal autocorrelations into PM 2.5 modeling [61]. Spatiotemporally autocorrelation benefits prediction of PM 2.5 , especially at the unmeasured locations but makes troubles for model evaluation.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, we also found that CV IS errors of PM 2.5 Optimal tended to be lower at the testing sites, which were surrounded by more training sites ( Figure 5). Similar findings have been reported in previous studies, which introduced spatial or spatiotemporal autocorrelations into PM 2.5 modeling [61]. Spatiotemporally autocorrelation benefits prediction of PM 2.5 , especially at the unmeasured locations but makes troubles for model evaluation.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, in a comparison between IDW-adjusted CTM and MLR, IDW-adjusted CTM (R 2 value = 0.510 per year) performed better than MLR (R 2 value = 0.330 per year) [62,67]. Lee et al [63] made a comparison between the Kriging method and CTM in the United States. Although both methods gave consistent results, CTM had better applicability and higher accuracy, especially in areas with few ground level monitoring sites.…”
Section: Theory Background and Applicationmentioning
confidence: 99%
“…Approaches that have been developed to simulate the distribution of the concentration of air pollutants usually include geostatistical interpolation [30], land-use regression [31], dispersion [32], and hybrid [33] models. "Dispersion models use information on emissions, source characteristics, chemical and physical properties of the pollutants, topography, and meteorology to model the transport and transformation of gaseous or particulate pollutants through the atmosphere to predict, e.g., ground level concentrations" [34].…”
Section: Lur Modelmentioning
confidence: 99%